2020
DOI: 10.1182/blood-2020-141785
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Chemogenetic Profiling Identifies Candidate Biomarker Genes That Modulate Sensitivity to Selinexor

Abstract: Introduction Selinexor (KPT-330) is a first-in-class selective inhibitor of XPO1-mediated nuclear export that has recently been approved by the US FDA for the treatment of relapsed/refractory multiple myeloma and relapsed diffuse large B-cell lymphoma. Additionally, the drug is being evaluated in ongoing clinical trials (phase I to III) on late-stage haematological and solid tumours. To improve outcomes and personalize therapeutics, specific biomarkers and underlying mechanisms of response to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They found that combination with proteasome inhibitors re-sensitized cells to selinexor, indicating that resistance might be overcome through drug combination regimens [ 119 ]. Ongoing work is focused on identifying molecular pathways involved in resistance to XPO1 inhibition, such as increased NF-kB signaling, TGF-β/SMAD pathway, and ESF1 transcription activity of G1/S cell cycle [ 120 , 121 , 122 , 123 ].…”
Section: Development Of Selective Inhibitors Of Nuclear Export For Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that combination with proteasome inhibitors re-sensitized cells to selinexor, indicating that resistance might be overcome through drug combination regimens [ 119 ]. Ongoing work is focused on identifying molecular pathways involved in resistance to XPO1 inhibition, such as increased NF-kB signaling, TGF-β/SMAD pathway, and ESF1 transcription activity of G1/S cell cycle [ 120 , 121 , 122 , 123 ].…”
Section: Development Of Selective Inhibitors Of Nuclear Export For Cancer Treatmentmentioning
confidence: 99%
“…Specifically in neuroblastoma, XPO1 protein expression and RNA expression do not correlate with sensitivity to selinexor [ 30 ]. However, recent efforts have explored XPO1 cargo localization and function, such as those listed in Table 1 , as predictors of response to XPO1 directed therapy [ 121 , 139 ]. For example, in gastric cancer, the presence of functional TP53 in the nuclear compartment seems to be crucial to promoting TP53-dependent apoptosis with XPO1/proteasome co-inhibition [ 140 ].…”
Section: Future Potential Of Xpo1 Inhibition In Pediatric Oncologymentioning
confidence: 99%
See 1 more Smart Citation